Bias Gender Sebagai Prediktor Kekerasan Dalam Rumah Tangga - Anugriaty Indah Asmarany (Jurnal Psikologi, 2008)
This article presents a meta‐analysis of the survey literature that has examined gender bias as predictors of domestic violence. A meta – analysis of 62 studies from 35 articles, 33 researchers and 53423 subjects evaluated the correlation between gender bias and domestic violence. This analysis extends previous work by directly correcting error of sampling and measurements. Summary analysis provided support for the hypothesis that gender bias has a correlation on domestic violence. The results showed gender bias have been identified as predictors of the domestic violence Keywords: meta‐analysis, domestic violence, gender bias